Cultivating Anti-Racism Allies in Academic Medicine (Mary Ann Liebert, 2023)
Racial microaggressions, racially based remarks, or actions that negatively impact marginalized physicians of color (Black, Latino/a/x, and American Indian/Alaskan Natives) often go unaddressed. This article provides four strategies for how individuals and institutions can engage in anti-racism allyship: (1) be an upstander during microaggressions, (2) be a sponsor and advocate for physicians of color, (3) acknowledge academic titles and accomplishments, and (4) challenge the idea of a ?standard fit? for academic faculty and research. Skills in academic allyship should be taught to all physicians throughout the educational continuum to mitigate feelings of isolation that racialized minority physicians frequently experience.